2020
DOI: 10.1038/s41431-020-00788-4
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of clinical criteria and high-throughput sequencing for diagnosing children with syndromic craniosynostosis

Abstract: An accurate diagnosis of syndromic craniosynostosis (CS) is important for personalized treatment, surveillance, and genetic counselling. We describe detailed clinical criteria for syndromic CS and the distribution of genetic diagnoses within the cohort. The prospective registry of the Norwegian National Unit for Craniofacial Surgery was used to retrieve individuals with syndromic CS born between 1 January 2002 and 30 June 2019. All individuals were assessed by a clinical geneticist and classified using defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 48 publications
3
20
0
Order By: Relevance
“…In the Oxford survey [17], pathogenic variants in 20 rarely involved genes accounted for 23/666 (3.5%) of all cases, and in the exome/genome sequencing study [20], the 15 new diagnoses were identified in 14 different genes. A recent study from Norway reported similar findings [21]. As we expect the patients enrolled into 100kGP to be enriched for rare genetic causes, this heterogeneity presents a substantial challenge for pipeline-based diagnosis, so we considered that CRS could represent a stringent test of how well the GE/GMC pipeline worked.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…In the Oxford survey [17], pathogenic variants in 20 rarely involved genes accounted for 23/666 (3.5%) of all cases, and in the exome/genome sequencing study [20], the 15 new diagnoses were identified in 14 different genes. A recent study from Norway reported similar findings [21]. As we expect the patients enrolled into 100kGP to be enriched for rare genetic causes, this heterogeneity presents a substantial challenge for pipeline-based diagnosis, so we considered that CRS could represent a stringent test of how well the GE/GMC pipeline worked.…”
Section: Introductionsupporting
confidence: 53%
“…Our analysis of CRS may not be representative of 100kGP data overall. Craniosynostosis likely represents a stringent test of the GS pipeline, given the extensive prior molecular and phenotypic screening undertaken before case recruitment (Box S1), and because CRS is known to be associated with a long tail of rare genetic diagnoses [17,21]. The reliance of GE/GMC on a panelbased diagnostic approach was evidently not well suited to this scenario.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, seizures are rarely observed in patients with CHD4 variants and occur only in a minority of patient with CHD3 alterations. Also craniosynostosis has been rarely reported in association with variants in other CHD genes (Siakallis et al 2019 ; Tønne et al 2020 ). In our cohort, craniosynostosis was observed in two individuals belonging to different families and in one patient with a de novo variant.…”
Section: Discussionmentioning
confidence: 99%
“…Disease‐causing heterozygous loss‐of‐function variants of ERF were first described in 2013, in 12 families segregating features of a newly recognized syndrome (termed ERF ‐related craniosynostosis or craniosynostosis type 4, OMIM# 600775), characterized by premature fusion of the cranial sutures (craniosynostosis), hypertelorism, and mild midface hypoplasia (Twigg et al, 2013). Confirmatory case reports have followed (Chaudhry et al, 2015; Korberg et al, 2020; Lee et al, 2018; Provenzano et al, 2021; Timberlake et al, 2017; Tønne et al, 2020; Yoon et al, 2020), and the clinical features of the disorder were further delineated and summarized in 16 additional families by Glass et al (2019). In addition to craniosynostosis and facial dysmorphism, additional frequently associated features included Chiari‐1 malformation, speech and language delay, poor gross and/or fine motor control, hyperactivity, and poor concentration.…”
Section: Brief Reportmentioning
confidence: 94%